2017
DOI: 10.1177/1045389x17704916
|View full text |Cite
|
Sign up to set email alerts
|

Extending the dynamic range of an energy harvester with a variable load resistance

Abstract: Abstract. In some energy harvesters, the maximum throw of the seismic mass is limited due to the physical constraints of the device. The shunt load resistance of such a harvester is generally selected based on the allowable throw of the mass when the device is subjected to the maximum level of excitation. However, the energy harvester with this value of shunt resistance does not perform well at lower levels of excitation. In this paper, a variable load resistance, scheduled on the excitation level, is introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It also mentioned that the internal resistance of this energy harvester depends on the number of cycles of input sinusoidal wave. While for the electromagnetic harvester, Hendijanizadeh et al [61] installed an intelligent control device to switch between cubic and linear load resistance to optimise the power output of the electromagnetic energy harvester in different frequencies and amplitude excitations condition in the actual environmental state. The result of the study showed that the internal resistance of the electromagnetic plays a significant role in choosing the maximum load resistance for the energy harvesting system and it must be recognized in the control technique design.…”
Section: Low Energy Harvesting Devicesmentioning
confidence: 99%
“…It also mentioned that the internal resistance of this energy harvester depends on the number of cycles of input sinusoidal wave. While for the electromagnetic harvester, Hendijanizadeh et al [61] installed an intelligent control device to switch between cubic and linear load resistance to optimise the power output of the electromagnetic energy harvester in different frequencies and amplitude excitations condition in the actual environmental state. The result of the study showed that the internal resistance of the electromagnetic plays a significant role in choosing the maximum load resistance for the energy harvesting system and it must be recognized in the control technique design.…”
Section: Low Energy Harvesting Devicesmentioning
confidence: 99%
“…It was demonstrated that the piecewise nonlinear stiffness behaviour, developed due to the interactions of the moving magnet's flux on the coil, facilitated the response of the system in a wider frequency range, enabling it to generate more electrical energy. Similarly, system damping characteristics have been employed in optimising the energy harvested by vibration energy harvesters [16][17][18][19][20][21][22][23][24]. In [16], the authors presented an unconventional way of achieving a tuneable resonant frequency (from high frequency to ultralow frequency) and extending both the bandwidth and peak of the energy harvested, simultaneously, by utilising a distinct structurally supported displacement-dependent nonlinear damping property.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], the authors presented an unconventional way of achieving a tuneable resonant frequency (from high frequency to ultralow frequency) and extending both the bandwidth and peak of the energy harvested, simultaneously, by utilising a distinct structurally supported displacement-dependent nonlinear damping property. This work was further extended by the authors in [17], Similarly, system damping characteristics have been employed in optimising the energy harvested by vibration energy harvesters [16][17][18][19][20][21][22][23][24]. In [16], the authors presented an unconventional way of achieving a tuneable resonant frequency (from high frequency to ultralow frequency) and extending both the bandwidth and peak of the energy harvested, simultaneously, by utilising a distinct structurally supported displacement-dependent nonlinear damping property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a look-up table is used for tuning based on a priori knowledge of the harvester. More recently, a similar approach was presented in [17] for extending the dynamic range of a harvester when the input displacement and frequency are variable. However, this approach utilizes an experimental model of the system.…”
Section: Introductionmentioning
confidence: 99%